2016
DOI: 10.1111/jonm.12413
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary public perceptions of nursing: a systematic review and narrative synthesis of the international research evidence

Abstract: A long-term, strategic solution is required that focuses on public engagement and interaction with the profession in a context wider than personal health/ill-health, and that goes beyond the marketing campaigns seen in the past to address recruitment crises.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
118
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(122 citation statements)
references
References 38 publications
1
118
0
3
Order By: Relevance
“…According to Cabaniss (), popular conceptions of the profession are often outdated and frequently depict an image that harks back to a non‐existent halcyon past in which selfless young women assisted heroic male physicians. A recent review of twenty‐one studies by Girvin, Jackson, and Hutchinson () found similar misconceptions about the work of nurses, which were also echoed by Tuckett, Kim, and Huh () and Glerean, Hupli, Talman, and Haavisto (). If, as seems likely, applicants draw on this pool of cultural information when considering entry to the profession, it is hardly surprising that they may feel overwhelmed when faced with the reality of clinical work.…”
Section: Responding To the Challengementioning
confidence: 74%
“…According to Cabaniss (), popular conceptions of the profession are often outdated and frequently depict an image that harks back to a non‐existent halcyon past in which selfless young women assisted heroic male physicians. A recent review of twenty‐one studies by Girvin, Jackson, and Hutchinson () found similar misconceptions about the work of nurses, which were also echoed by Tuckett, Kim, and Huh () and Glerean, Hupli, Talman, and Haavisto (). If, as seems likely, applicants draw on this pool of cultural information when considering entry to the profession, it is hardly surprising that they may feel overwhelmed when faced with the reality of clinical work.…”
Section: Responding To the Challengementioning
confidence: 74%
“…Individual nurses just aren't as compassionate as they used to be. Explanations in terms of personal moral failure (The 'Bad Apple ' -Traynor et al 2014) find some favour with a public influenced by press coverage which tends to portray nursing as a 'troubled' profession (Girvin et al 2016), reinforced by some scepticism about the value of graduate preparation and professional status (Gillett 2012). Politicians have also been quick to point the finger at the profession of nursing and individual nurses.…”
Section: Mid Staffordshire Nhsft and The Compassion Deficit In Nursesmentioning
confidence: 99%
“…In addition, the role of nursing education institutions is vital in shaping the nursing identity. Freshmen nursing students mainly re ect the general viewpoint of society as they only have a limited understanding about nursing [15,26,27]. A study conducted in Turkey demonstrated that students didn't have su cient knowledge regarding nursing at the beginning of their education, while an introduction to a nursing course has improved the students' understanding of the nursing profession [27].…”
Section: Introductionmentioning
confidence: 99%